FAS APOPTOTIC GENE POLYMORPHISM (-670A/G) IS ASSOCIATED WITH CLINICAL PHENOTYPES OF SYSTEMIC SCLEROSIS IN A RUSSIAN POPULATION: A PILOT STUDY - M. Yu. Krylov; L. P. Ananyeva; O. A. Koneva; M. N. Starovoitova; E. Yu. Samarkina; O. V. Desinova; O. B. Ovsyannikova; E. N. Aleksandrova; A. A. Novikov; I. A. Guseva (Научно-практическая ревматология, 2017)
The FAS antigen (Apo-1/CD95) is a key molecule of apoptosis in most cell types, including activated immune cells and fibroblasts. The FAS gene promoter region contains a single-nucleotide polymorphism (-670A/G) associated with a substitution of the nucleotide arginine for guanine, which is associated with the predisposition to systemic lupus erythematosus, multiple sclerosis, sarcoidosis, and autoimmune hepatitis.Objective: to test the hypothesis that the FAS -670А/G polymorphism may predispose to systemic sclerosis (SS), its clinical and autoimmune phenotypes in a Russian patient sample.Subjects and methods. The instigation enrolled 90 SS patients who were classified according to clinical and autoimmune phenotypes. A control group consisted of 152 apparently healthy unrelated individuals matched for sex and age. The FAS -670А/G polymorphism was studied by polymerase chain reaction, followed by restriction fragment length polymorphism analysis.Results and discussion. A relatively small sample of Russian patients showed no statistically significant association of the studied FAS -670 A/G polymorphism with the predisposition to SS as a whole and the majority of its clinical and immunological phenotypes. There was a statistically significant positive association of the G allele (the FAS -670 GG+GA genotype) with the presence of digital ulcers and the chronic course of the disease. The G allele (the FAS -670 GG+ GA) was detected less frequently in patients with interstitial lung disease (ILD) than in those without ILD.Conclusion. The findings show that the FAS -670A>G polymorphism plays a role in the predisposition to some clinical phenotypes of SS in Russian patients.